Black Metal Istiqomah Dakwah "Hitam" di Media Sosial - M Syendi Apriko (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2020)
Media supporting da'wah is not only limited to the pulpit of the mosque but has come in contact with modern communication technology, especially the use of the internet. This ease has an impact on the number of users from social media who actively share da'wah content so that it becomes viral. Another da'wah phenomenon that attracted the attention of researchers was the 'black' da'wah uploaded on social media by the Black Metal Istiqomah account through both social media Facebook and Instagram. On Instagram, this account has the name of the shadow Al-Varokah Nur Vahalla with followers of more than 16 thousand and the number of posts as many as 179. Researchers discuss further uploaded by this account and view it from the point of view of visual communication using theories that have been tested and use qualitative methods. There are several visual techniques used in Black Metal Istiqomah including; shading techniques, Dussel techniques, pointillary techniques, collage techniques and dry techniques. Work in the form of; comic stip, prayer illustration, typography made with the shape and style of Black metal music. In conclusion, the style of Black metal that is used only as an artistic form of attraction in order to create different nuances in conveying da'wah messages to young people has nothing to do with the heretical and negative schools which have been attached to Black metal music.